Localised pulmonary resection for bronchiectasis in hypogammaglobulinaemic patients. Issue 5 (May 1994) - Cohen, A J; Roifman, C; Brendan, J; Mullen, M; Reid, B; Weisbrod, G; Downey, G P
Abstract : BACKGROUND–Bronchiectasis and pulmonary infections are common in patients with hypogammaglobulinaemia. Despite intravenous gammaglobulin treatment and appropriate antibiotics, a subgroup of patients remains with persistent localised pulmonary infection in segments where bronchiectasis had developed before appropriate treatment. As such localised pulmonary suppuration (segmental or lobar) may serve as a focus for progression of bronchiectasis, surgical resection of the involved segments may be considered. The outcome of pulmonary resection in four such patients is reported. RESULTS–Surgery was well tolerated except for one postoperative empyema. Information on follow up is available from 3.5 to 5 years. All patients experienced considerable reduction of symptoms including cough, sputum production, antibiotic use, and hospital admissions. CONCLUSIONS–Surgical resection of localised bronchiectatic segments should be considered in patients with hypogammaglobulinaemia with persistent localised suppuration and symptoms refractory to medical treatment.